Velleius Paterculus and the Roman Senate at the Beginning of the Principate - Markelov, Andrei Y. (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The “Roman history” by Velleius Paterculus is the sole historiographical work written by a contemporary of Augustus and Tiberius. The paper deals with representation of the Roman Senate of Velleius’ time in his work. I argue that in his compendium the historian reflected the ambivalent position of the Senate under the first two Roman Emperors. He depicts the institution as more passive in comparison with its description in the previous period and as depending on the Princeps. At the same time this Roman author characterizes the Senate as having maiestas, the notion which was not connected with this authority under the Republic. Assigning of maiestas to the Senate by Velleius reflects a deep change in the position of the curia due to decline of the popular assemblies’ significance at the beginning of the Principate.